Identification of two binding partners for the bacterial actin homolog MreB - Buske, Paul (My University, 2007)
A distinguishing characteristic of prokaryotes was long thought to be the lack of a cytoskeleton similar to eukaryotes consisting of actin filaments, microtubules, and intermediate filaments. However, recent work has shown the existence of bacterial proteins homologous to the eukaryotic cytoskeleton. One such protein, MreB (murein cluster e), encircles the bacterial cell and exhibits structural homology to actin. Because of the homology between MreB and actin and the many interacting proteins with which actin has in its various cellular functions, we hypothesized MreB also interacts with many proteins in the bacterial cell. Preliminary interaction tests using light scattering fluorometry and co-sedimentation assays show interactions between purified E. coli MreB and the His-tagged proteins NusG and EF-Tu, with work still to be done on identification of other interacting partners and the biochemical nature of theses interactions.
25 p.
Keywords: Biochemistry; Zoology